2010
DOI: 10.1103/physrevb.82.054513
|View full text |Cite
|
Sign up to set email alerts
|

Flux dynamics associated with the second magnetization peak in the iron pnictideBa1xKxFe2As<

Abstract: We report on isofield magnetic relaxation data on a single crystal of Ba 1−x K x Fe 2 As 2 with superconducting transition temperature T c = 32.7 K which exhibit the so-called fish-tail effect. A surface map of the superconducting transition temperature shows that the superconducting properties are close to homogeneous across the sample. Magnetic relaxation data, M͑t͒, was used to obtain the activation energy U͑M͒ in order to study different vortex-dynamics regimes. Results of this analysis along with time-dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
96
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 33 publications
24
96
4
Order By: Relevance
“…4(a). The evaluated value of µ is ∼ 1.34 close to that reported in YBa 2 Cu 3 O 7−δ [33], and IBSs [10,12,20]. The value of µ resides between the prediction of singlevortex (1/7) and small-bundle (5/2) regimes, indicating that contributions of those two kinds of pinnings coexist.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…4(a). The evaluated value of µ is ∼ 1.34 close to that reported in YBa 2 Cu 3 O 7−δ [33], and IBSs [10,12,20]. The value of µ resides between the prediction of singlevortex (1/7) and small-bundle (5/2) regimes, indicating that contributions of those two kinds of pinnings coexist.…”
supporting
confidence: 79%
“…Magnetic relaxation measurements in IBSs reported so far have revealed that they also show giant flux creep and collective pinning, which implies that IBSs and cuprate superconductors may share common vortex physics [7][8][9][10][11][12][13]. Until now, most detailed studies about the vortex dynamics on IBSs have been performed on "122" phase since high-quality single crystals are readily available.…”
mentioning
confidence: 99%
“…23,24 However, significant differences in the second-peak features have been observed within this family: in the highly anisotropic Bi-2212 and Bi-2223 the peak is sharp and temperature independent [25][26][27][28][29] while in Bi-2201 crystals it exhibits a strong temperature dependence. 30 Regarding the iron-based superconductors, the peak effect has been observed in FeAs-1111, [31][32][33] in FeAs-122, [34][35][36][37][38] and in FeTe 1−x Se x , 39 even if a clear understanding of the physical origin of the phenomenon in this family has not been achieved yet. However, since it has been shown by small angle neutron scattering, [40][41][42] Bitter decoration, 40 and magnetic force microscopy 41 that an ordered vortex lattice is not present in these compounds, the origin of the peak effect due to a phase transition of the vortex lattice seems to be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of H irr (T ) values lying well below the H c2 (T ) values over the entire H-T vortex phase diagram has been a distinct feature seen in a wide variety of low-T c and high-T c superconductors [33][34][35][36][37][38][39]. Here it is worthwhile to look at its ramifications on the exponents within the Dew-Hughes scenario for the iron chalcogenide superconductor under consideration.…”
mentioning
confidence: 99%